Medicinal Chemists of the 21st Century—Who Are We and Where to Go?. Issue 7 (29th April 2015) - Nussbaumer, Peter
Abstract Many recent articles have dealt with the future challenges in medicinal chemistry. Here, I discuss my concerns over the future of medicinal chemists, who have to be skilled and knowledgeable in many different fields, particularly in the context of the ever‐growing requirements, the request for even broader diversification, and the substantial structural change in industrial drug discovery. In my opinion, we have to do the following in order to ensure sustained high quality and achievements: 1) to focus on superior design without excluding complex structures a priori; 2) to proactively shape the future of our discipline; 3) to discuss specialization; 4) to intensify exchange between academia and industry; and 5) to remodel education of the next generation of medicinal chemists. By providing my opinion on these aspects, I hope to stimulate discussions and change within the community.